Assessing the European offshore wind and wave energy resource for combined exploitation. (February 2017) - Kalogeri, Christina; Galanis, George; Spyrou, Christos; Diamantis, Dimitris; Baladima, Foteini; Koukoula, Marika; Kallos, George
Abstract: The main concern when utilizing renewable energy resources is their intermittency and variability. One way to deal with this shortcoming is to harvest energy from complementary sources. In this study, wind and wave energy were selected as such and further analyzed in terms of availability, variability, coherence, correlation and potential impact from extreme values. This resource characterization was performed in different timescales, during a 10-year period, using high resolution numerical modeling systems. Based on the results of this analysis, the most suitable areas for combined exploitation were identified and the possible merits from this synergy were pin-pointed and discussed. It was indicated that the most suitable areas for combined use are the western offshore areas of Europe. The wind and wave fields in these open sea areas reveal the lowest correlation in the examined field in contrast to those located in semi-enclosed and enclosed basins that exhibit the highest ones. The joint exploitation in the former regions gives a less variable power output with considerable fewer hours of zero production. Moreover, the suitable energy conversion system for a specific area is strongly dependent on the local characteristics of the available resource. Highlights: Assessing the spatiotemporal variability of the European offshore wind and wave energy resources. Areas favorable for combined exploitation were pin pointed. The most important benefits from the combined use were identified. The differences in using different type of combined wind and wave energy converters in areas with different climatological characterisitcs were highlighted.